RESOLUSI KONFLIK PEMBANGUNAN ISLAMIC CENTER DAN MASJID AT-TAQWA MATARAM - udin, Najam (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2018)
The con?ict in utilizing the NTB Islamic Center mosque and At-Taqwa Great Mosque gave rise to diverse responses in the community, especially from the Tabligh Jamaah group who previously managed the At-Taqwa Mataram Grand Mosque as the center of its activities. Despite the fact that activities in the Great Mosque have been moved to the Islamic Center, the Mataram Great Mosque is still used as a means by the Tablighi Jamaah. This research is a feld research using a qualitative approach. So if you look at it with Scannell’s theory of con?ict, where con?ict is a natural and normal thing that arises because of differences in perception. Therefore, the construction of houses of worship should be based on the principle of how to realize the benefts in life in the world and in the hereafter. Con?ict Resolution Against the Con?ict of Islamic Center Development and and the use of the nearby Mataram At-Taqwa Mosque (converted into other functions) also reap polemics, mainly because the land status of the mosque is a waqf land for the mosque. Associated with the status of land waqf, then communication efforts are intensive with the interpreter so as not to cause misunderstandings among the apostate families.